(3GdEOGQI GdESJQGJjLjIs - (3eUWai jhSa(B, (3cGajs; (3eMeO WGgQ GdNda(B, (3gHI eUWai cGajs ((3bSfWjfI(B:s (3CdaG ddhKGFb(B,s, 2017)
-(3eaghe GdEOGQI GdESJQGJjLjI (B-(3GdJacjQ GdGSJQGJjLj (B-(3eGgjI GdeOjQ GdGSJQGJjLj (B-(3JaYjd GdeOjQ GdGSJQGJjLj GdCOGA (B-(3GdJhLg GdGSJQGJjLj (B-(3GdESJQGJjLjGJ GdhXjajI (B-(3GdJMdjd GdGSJQGJjLj hYhGedg (B-(3GdJNWjW GdGSJQGJjLj hGdHjFI (B-(3GdQbGHI GdESJQGJjLjI (B-(3GdJhLjg GdQjGOj (B-(3caGAI GdCOGA aj GdefXeGJ GdESJQGJjLjI (B-(3HWGbI GdCOGA GdeJhGRf fXGe eJcGed dUjjGZI hJfajP hJbjje GdESJQGJjLjI (B-(3GdEOGQI GdESJQGJjLjI ddLhOI GdTGedI hGdCOGA GdeJejR (B-(3GdgfOQI eWdH GSJQGJjLj dRjGOI GdbOQI GdJfGaSjI ddefXGe(B.s
(3HHdjhZQGajG(B:(3U(B.291s
Keywords: (3GdEOGQIs; (3GdESJQGJjLjIs; (3GdJhLjgs